Hawking-Unruh Hadronization and Strangeness Production in High Energy Collisions - Paolo Castorina; Helmut Satz (Advances in High Energy Physics)
The thermal multihadron production observed in different high energy collisions poses many basic problems: why do even elementary, e+e- and hadron-hadron, collisions show thermal behaviour? Why is there in such interactions a suppression of strange particle production? Why does the strangeness suppression almost disappear in relativistic heavy ion collisions? Why in these collisions is the thermalization time less than ≃0.5 fm/c? We show that the recently proposed mechanism of thermal hadron production through Hawking-Unruh radiation can naturally answer the previous questions. Indeed, the interpretation of quark (q)-antiquark (q̅) pairs production, by the sequential string breaking, as tunneling through the event horizon of colour confinement leads to thermal behavior with a universal temperature, T≃170 Mev, related to the quark acceleration, a, by T=a/2π. The resulting temperature depends on the quark mass and then on the content of the produced hadrons, causing a deviation from full equilibrium and hence a suppression of strange particle production in elementary collisions. In nucleus-nucleus collisions, where the quark density is much bigger, one has to introduce an average temperature (acceleration) which dilutes the quark mass effect and the strangeness suppression almost disappears.